The Synthesis of Glutaraldehyde-modified Chitosan Utilizing MAOS (Microwave Assisted Organic Synthesis) Method as Adsorbent of Pb(II) Ions Contained in Water Sample of Cikapundung River - Bandung - Herayati, Herayati; Wahyuningrum, Deana (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2020)
Indonesia has a vast territory. Approximately 2/3 of Indonesia is water. Indonesia has almost 6% of the world's water resources or approximately 21% of water resources in the Asia Pacific region. Indonesian waters comprise 97.4% seas and 2.6% are rivers, lakes and straits. There are 309 rivers in Indonesia and 49 of them flow through Bandung; one of them is Cikapundung River. Pb(II) ions contained in Cikapundung River has exceeded the quality standard of water river. Therefore, it is necessary to reduce the amount of Pb(II) ions from the river. One of the solutions is by using biodegradable adsorbent, the glutaraldehyde-modified chitosan. Chitosan was obtained from deacetylation of chitin in basic condition. The chitosan was characterized using FTIR showed 85.5% degrees of deacetylation. The other characterization is determination of average molecular mass using Ostwald viscometry method, obtained the average molecular mass of chitosan is 2.7 x 106 g/mol. Furthermore, chitosan was modified by reacting with glutaraldehyde using MAOS (Microwave Assisted Organic Synthesis) method at 80℃ with irradiation power of 100 W for 60 minutes to form glutaraldehyde-modified chitosan with 79% degree of substitution. The synthesized glutaraldehyde-modified chitosan was characterized by FTIR, SEM, SAA and applied as adsorbent of Pb(II) ions. The results showed that the optimum condition of adsorption for 15 mL of Pb(II) solution was achieved at pH 4 using 0.075 grams of adsorbent and 90 minutes of contact time. The adsorption process of Pb(II) ions follows the Langmuir isotherm model and the pseudo-second order kinetics with percent adsorption of Pb(II) ions from the water sample of Cikapundung river is 84% and 50.2%, for sample collected from middle-stream and downstream of river, respectively.